2016
DOI: 10.1371/journal.pone.0159507
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation and Genetic Instability in Monosomy Blastocysts May Contribute to Decreased Implantation Potential

Abstract: DNA methylation is a key epigenetic mechanism responsible for gene regulation, chromatin remodeling, and genome stability, playing a fundamental role during embryonic development. The aim of this study was to determine if these epigenetic marks are associated with chromosomal aneuploidy in human blastocysts. Surplus, cryopreserved blastocysts that were donated to research with IRB consent were chosen with varying chromosomal aneuploidies and respective implantation potential: monosomies and trisomies 7, 11, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The results of this study obtained from validation phase showed a significant decrease in the methylation level in the case compared to the control groups in all CpGs, which related to TYRO3, CGβ, and FAM189A1 gene‐related amplicon. Each one of this CpGs was located in gene bodies and CpG islands, and these genes were found to be related to spermatogenesis and male fertility (Berger et al., ; Chen et al., ; McCallie et al., ; Parrott, Sriram, Liu, & Mathews, ). In general, our results are in agreement with the results of previous studies that have shown a variation at sperm DNA methylation in subfertile males compared to normal males (El Hajj et al., ; Kläver et al., ; Montjean et al., ) and in addition to other studies that report males suffering from reduced fecundity have low levels of sperm DNA methylation compared to their counterparts of proven fertility (Aoki, Emery, & Carrell, ; Boissonnas et al., ; Ferfouri et al., ; Laqqan, Solomayer, & Hammadeh, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study obtained from validation phase showed a significant decrease in the methylation level in the case compared to the control groups in all CpGs, which related to TYRO3, CGβ, and FAM189A1 gene‐related amplicon. Each one of this CpGs was located in gene bodies and CpG islands, and these genes were found to be related to spermatogenesis and male fertility (Berger et al., ; Chen et al., ; McCallie et al., ; Parrott, Sriram, Liu, & Mathews, ). In general, our results are in agreement with the results of previous studies that have shown a variation at sperm DNA methylation in subfertile males compared to normal males (El Hajj et al., ; Kläver et al., ; Montjean et al., ) and in addition to other studies that report males suffering from reduced fecundity have low levels of sperm DNA methylation compared to their counterparts of proven fertility (Aoki, Emery, & Carrell, ; Boissonnas et al., ; Ferfouri et al., ; Laqqan, Solomayer, & Hammadeh, ).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are expressed on the surface of B cells which are important for antibody response. With pregnancy being a pro‐inflammatory state, proper expression of these proteins would be required for successful implantation to occur (McCallie et al., ). The alteration in the level of methylation may lead to changes in the activity and function of the gene especially CGB and TYRO3, which affects the spermatogenesis process and semen parameters, and this is consistent with the hypothesis that observed that the variations in methylation status are the possible reason for the abnormality in semen parameters of subfertile males and change in the gene expression (Miller‐Lindholm, LaBenz, Ramey, Bedows, & Ruddon, ; Lu & Lemke, ; Uusküla et al., ; van der Gun et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…McCallie et al sequenced the global methylation patterns of 316 cryopreserved aneuploid blastocysts, which were compared with control euploid blastocysts utilizing the Infinium Human-Methylation 450K BeadChip. 73 Significant hypomethylation of regulatory genes coding for DNA methyltransferases, chromatin modifying regulators, and posttranslational modifiers were observed in monosomic but not trisomic or euploid embryos. Given the diminutive reproductive potential of monosomic embryos, such findings highlight a potential epigenetic contribution to aneuploidy.…”
Section: Epigenetic Aberrancies and Aneuploidymentioning
confidence: 99%
“…In an earlier study, no differences were found in the DNA methylation profile of blastocysts with trisomy from euploid blastocysts, but in cases of monosomies, individual chromosomes with monosomy were hypermethylated. A decrease in DNA methylation has been recorded in several genes that are necessary for implantation and normal embryo development [79]. Moreover, along with a decrease in the level of gene methylation on chromosomes with monosomy, there was also a decrease in the transcription level of DNA methyltransferase genes.…”
Section: Dna Methylation and Aneuploidy At The Cleavage Stagementioning
confidence: 99%